STUDENTS LEARNING ACHIEVEMENTS - Irfan, Irfan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2014)
Abstract: The objective of this Research are to discover the correlation of motor ability, potential academic, physical fitness and learning motivation of learning achievement. This research was conducted by path analysis design. 100 students of FIK UNM Makassar were selected of 200 students by using simpel random sampling. Research findings reveal that ten of research hypotheses were supported, i.e. (H.1) there was an effect of motor ability on learning motivation students; (H.2) there was an effect of potential academic on learning motivation students; (H.3) there was an effect of physical fitness on learning motivation students; (H.4) there was an effect of motor ability on learning achievement students; (H.5) there was an effect of potential academic on learning achievement students; (H.6) there was an effect of physical fitness on learning achievement students; (H.7) there was an effect of learning motivation on learning achievement students; (H.8) there was an effect of motor ability on learning achievement by learning motivation students; (H.9) there was an effect of potential academic on learning achievement by learning motivaton students; (H.10) there was an effect of physical fitness on learning achievement by learning motivation student. Unsupported hypotheses were; (H.5) there was not an effect of potential academic on learning achievement students, (H.9) there was not an effect of potential academic on learning achievement by learning motivation students. The conclusion of this Research is that the learning motivation and learning achievement can increased by improving of motor ability, potential academic and physical fitness Abstrak: Tujuan dari penelitian ini adalah untuk menemukan korelasi kemampuan motorik, potensi akademik, kebugaran fisik dan motivasi prestasi belajar. Penelitian ini dilakukan dengan analisis jalur desain. 100 siswa dari FIK UNM Makassar dipilih dari 200 siswa dengan menggunakan simpel random sampling. Temuan penelitian menunjukkan bahwa sepuluh hipotesis penelitian yang didukung, yaitu (H.1) ada pengaruh kemampuan motorik pada motivasi belajar siswa; (H.2) ada pengaruh dari potensi akademik terhadap motivasi belajar siswa; (H.3) ada pengaruh dari kebugaran fisik pada motivasi belajar siswa; (H.4) ada pengaruh kemampuan motorik terhadap prestasi belajar siswa; (H.5) ada pengaruh dari potensi akademik terhadap prestasi belajar siswa; (H.6) ada pengaruh dari kebugaran fisik terhadap prestasi belajar siswa; (H.7) ada pengaruh motivasi belajar terhadap prestasi belajar siswa; (H.8) ada pengaruh kemampuan motorik terhadap prestasi belajar dengan motivasi belajar siswa; (H.9) ada pengaruh dari potensi akademik terhadap prestasi belajar siswa dengan motivasi belajar; (H.10) ada pengaruh efek kebugaran fisik terhadap prestasi belajar dengan motivasi belajar siswa. Hipotesis yang tidak didukung adalah; (H.5) tidak ada pengaruh dari potensi akademik terhadap hasil belajar siswa, (H.9) tidak ada pengaruh potensi akademik terhadap prestasi belajar dengan motivasi belajar siswa. Kesimpulan dari penelitian ini adalah bahwa motivasi belajar dan prestasi belajar dapat meningkat dengan meningkatkan kemampuan motorik, potensi akademik dan kebugaran fisik.